The Impact of Social Media on Group Decision-Making Processes: A Bibliometric Review - Hanifan Ega Pratama; Syahrul Safi’Uddin; Kalfizer Tappang; Reynaldi Reynaldi; Diky Diky; Chandika Mahendra Widaryo; Muhammad Ramadhani Kesuma (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study maps and analyses the scholarly literature on the impact of social media on group decision-making processes, with a particular focus on the human resource management (HRM) context, using a bibliometric approach. Data were retrieved from Scopus databases, yielding 116 peer-reviewed articles spanning 2006 to 2026. VOSviewer software was employed to visualise co-authorship networks and keyword co-occurrence patterns, enabling systematic mapping of collaboration structures and thematic evolution. The field exhibits substantial scientific impact, averaging 48.59 citations per document, and is characterised by extensive global collaboration. Thematically, research has evolved from a conceptual stage centred on trust and community interaction toward an applicative and computational stage dominated by big data, artificial intelligence (AI), and consensus model optimisation. Enterprise social media platforms have emerged as strategic infrastructure reinforcing collaboration and inclusivity in hybrid work environments, although challenges related to group bias amplification, polarisation, and echo chamber dynamics remain persistent. Organisations operating in digital and hybrid environments should strategically govern social media platforms to leverage collective intelligence while proactively mitigating algorithmic bias and polarisation risks in group decision-making. This is among the first bibliometric studies to specifically focus on the intersection of social media and group decision-making within an HRM context, identifying AI-driven decision architectures and digital bias mitigation as the most critical frontier for future research.